Is There a Woodwork Effect? Addressing a 200-Year Debate on the Impacts of Expanding Community-Based Services. Issue 1 (1st January 2019) - Berish, Diane; Nelson, Ian; Mehdizadeh, Shahla; Applebaum, Robert
ABSTRACT: In U.S. social welfare history, many have suggested that if benefits were too attractive, consumers would come out of the woodwork to take advantage of the opportunity. Clinical trials have provided evidence of the woodwork effect's existence, suggesting caution when expanding home- and community-based services (HCBS). However, it is unclear whether these studies are best suited to assess whether a system-level effect occurs. Using state and federal data tracking Ohio's long-term services and support (LTSS) system from 1995 to 2015, this paper examines changes in the utilization rates and expenditures of Medicaid LTSS to explore whether a woodwork effect occurred as Ohio moved to improve its LTSS system balance (80% Nursing Home [NH], 20% HCBS) to (49% Nursing Home [NH], 51% HCBS). After accounting for population growth of individuals older than 60 and those with two or more impairments in activities of daily living, there was no change in utilization rates of older people with severe disability (1995: 491 per 1000 population, 2015: 495 per 1000 population) or overall LTSS expenditures (1997: 2.7 million [in 2013 dollars], 2013: 2.9 million). Our results suggest that states can make significant strides in HCBS expansion without increasing the overall long-term services utilization rate.